Cell-Specific Expression Pattern of Toll-Like Receptors and Their Roles in Animal Reproduction - Atlı, Mehmet Osman; Hitit, Mustafa; Özbek, Mehmet; Köse, Mehmet; Bozkaya, Faruk (Springer International Publishing, 2022)
Toll-like receptors (TLRs), a part of the innate immune system, have critical roles in protection against infections and involve in basic pathology and physiology. Secreted molecules from the body or pathogens could be a ligand for induction of the TLR system. There are many immune and non-immune types of cells that express at a least single TLR on their surface or cytoplasm. Those cells may be a player in a defense system or in the physiological regulation mechanisms. Reproductive tract and organs contain different types of cells that have essential functions such as hormone production, providing an environment for embryo/fetus, germ cell production, etc. Although lower parts of reproductive organs are in a relationship with outsider contaminants (bacteria, viruses, etc.), upper parts should be sterile to provide a healthy pregnancy and germ cell production. In those areas, TLRs bear controller or regulator roles. In this chapter, we will provide current information about physiological functions of TLR in the cells of the reproductive organs and tract, and especially about their roles in follicle selection, maturation, follicular atresia, ovulation, corpus luteum (CL) formation and regression, establishment and maintenance of pregnancy, sperm production, maturation, capacitation as well as the relationship between TLR polymorphism and reproduction in domestic animals. We will also discuss pathogen-associated molecular patterns (PAMPs)-induced TLRs that involve in reproductive inflammation/pathology.
Keywords: Male; Reproduction; Follicular Atresia; Toll-Like Receptors; Reproductive cells; Toll-like receptors; Domestic animals; Pregnancy; Immune System; Animals; Humans; Female; Polymorphism; Spermatogenesis; 3. Good health